Magnesium sulfate as a key mineral for the detection of organic molecules on Mars using pyrolysis. Issue 1 (26th January 2016) - François, P.; Szopa, C.; Buch, A.; Coll, P.; McAdam, A. C.; Mahaffy, P. R.; Freissinet, C.; Glavin, D. P.; Navarro‐Gonzalez, R.; Cabane, M.
Abstract: Pyrolysis of soil or rock samples is the preferred preparation technique used on Mars to search for organic molecules up today. During pyrolysis, oxichlorines present in the soil of Mars release oxidant species that alter the organic molecules potentially contained in the samples collected by the space probes. This process can explain the difficulty experienced by in situ exploration probes to detect organic materials in Mars soil samples until recently. Within a few months, the Curiosity rover should reach and analyze for the first time soils rich in sulfates which could induce a different behavior of the organics during the pyrolysis compared with the types of soils analyzed up today. For this reason, we systematically studied the pyrolysis of organic molecules trapped in magnesium sulfate, in the presence or absence of calcium perchlorate. Our results show that organics trapped in magnesium sulfate can undergo some oxidation and sulfuration during the pyrolysis. But these sulfates are also shown to protect organics trapped inside the crystal lattice and/or present in fluid inclusions from the oxidation induced by the decomposition of calcium perchlorate and probably other oxychlorine phases currently detected on Mars. Trapped organics may also be protected from degradation processes induced by other minerals present in the sample, at least until these organics are released from the pyrolyzed sulfate mineral ( 700°C in our experiment). Hence, we suggest magnesium sulfate as one of the minerals to target in priority for the search of organic molecules by the Curiosity and ExoMars 2018 rovers. Key Points: Magnesium sulfate leads to oxidation of organic molecules during pyrolysis Trapped organics are protected from oxidation from perchlorate decomposition